THE FORMATION OF THE MECHANISM FOR STATE TOURISM MANAGEMENT AT THE REGIONAL LEVEL - Mukhamedovich Umarov, Murad; Aleksandrovich Sokolov, Dmitry; Vladimirovich Vlasov, Grigory; Vyacheslavovich Maslyukov, Andrey; Viktorovna Ukhina, Tatiana (Revista Inclusiones, 2021)
The article is devoted to the development of approaches to the formation of state tourism management at the regional level. It has been established that the specifics of regions determine in each case the possibility of using a certain set of methods, levers and incentives determined at the state level for regulating the development of the tourism sector. However, the responsibility for the formation and effective use should rest with the regional authorities.